Pentingnya Literasi Digital Pada Pendidikan Pekerjaan Sosial di Indonesia - Sugeng Pujileksono (Universitas Wijaya Kusuma Surabaya, 2022)
The Industrial Revolution 4.0 and Society 5.0 are marked by the massive use of the internet and artificial intelligence. As a result, some social work assistance processes have shifted to an online system. Such conditions demand social work education to equip students with digital skills. Research Purpose. This study tries to explain the importance of digital skills in social work education. Methods. This research method uses a literature study by reviewing various literature on digital literacy in social work education. Data Analysis. Data analysis was carried out by categorizing secondary data into themes. Social work education curricula must be responsive to the demands of digitalization in some social worker assistance practices. Result and Discussion. The use of ICT in social work education must refer to the standards formulated by professional organizations. Social work educators and students must be aware that digitizing social work practices is only a means of facilitating services, not an end. Conclusion. Digital literacy is a necessity in social work education. Therefore, it is necessary to prepare educators with digital skills and ethical standards for using ICT in social work education.Keywords: Digital Literacy, Information and Communication Technology, Social Work Education